KAJIAN ASPEK INTERIOR RUANG BELAJAR DAN BERMAIN PADA TAMAN KANAK-KANAK DI SURAKARTA - Prasetya, Natasha (Dimensi Interior, 2012)
One of the methods to increase the qualitiy of human resources is to improve education. As a formal pre-school education center, a kingergarden can contribute in building a strong foundation in a child’s development in terms of character, behaviour, knowledge, skill and creativity. Accomodating the activities and designing the facilities in the learning spaces are thus important factors to consider. The objective of this research is thus to investigate whether the interior design of the kindergardens in Surakarta have been designed to accommodate the learning activities effectively. TK Negeri Pembina Kecamatan Banjarsari and TK Kristen Kalam Kudus Surakarta have been chosen as case studies as they are the largest public and private schools repsectively. The research findings conveyed that the preschools in Surakarta have considered the learning aims adopted from the Deparment of National Education along with additional curriculums adapted by the schools’ foundations when desigining the interior of the learning and playing spaces.